2012
DOI: 10.1177/1477370812453401
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual exploitation and youth offending: A research note

Abstract: Links between child sexual exploitation (CSE) and youth offending should be better recognised, according to these preliminary research findings from the UK. Data from a leading CSE service provider and Youth Offending Team were analysed for the period 2001–2010 inclusive. Of CSE victims, 40 percent had offending records and recidivism rates were high. Together they committed 1586 offences – 5 percent of all local youth crime. Male and female offending behaviour differed significantly. The types of offences ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 3 publications
5
13
0
Order By: Relevance
“…Many of our findings resonate with previous research in which associations have been documented qualitatively and to a lesser extent quantitatively between CSE and youth offending, going missing and being in care (e.g., Beckett, 2011;Brayley and Cockbain, 2012;CEOP, 2011;Clutton and Coles, 2007;Jago et al, 2011;OCCE, 2012;Pearce, Williams & Galvin, 2003;Scott and Skidmore, 2006). In what appears to be an isolated example of prior research covering CSE referral pathways in the UK,…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many of our findings resonate with previous research in which associations have been documented qualitatively and to a lesser extent quantitatively between CSE and youth offending, going missing and being in care (e.g., Beckett, 2011;Brayley and Cockbain, 2012;CEOP, 2011;Clutton and Coles, 2007;Jago et al, 2011;OCCE, 2012;Pearce, Williams & Galvin, 2003;Scott and Skidmore, 2006). In what appears to be an isolated example of prior research covering CSE referral pathways in the UK,…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, 10% of male and 4% of female service users were suspected of being involved in knife or gun crime (among the 46% of cases of which this information was known). These results corresponded with our expectations due to their close parallels to findings from Cockbain and Brayley's (2012) localised study. They found that 48% (n=53) of male and 35% (n=158) of female CSE service users in an English city, Derby, had criminal records.…”
Section: Youth Offendingsupporting
confidence: 93%
See 1 more Smart Citation
“…The CSE service does not. What we see is that items involving violent, destructive and/or potentially offending behaviour are present only in assessments for HSB cases, despite research suggesting that children and young people who experience or are vulnerable to CSE may display similar behaviours (Cockbain and Brayley, ). That this is embedded in the HSB recording, but not the CSE recording, may evidence a generalised focus on HSB as being part of a pattern of risk (to others), compared to a view of CSE as part of a pattern of vulnerability.…”
Section: Discussionmentioning
confidence: 64%
“…Sharpe (2012:62), for example, through interviews with 52 young women involved in the CJS in the UK, makes connections between girls' experiences of family conflict and convictions for 'offending' at home. On top of this, girls who offend often grow up in neighbourhoods with few prosocial peers and opportunities (Sharpe, 2012), leading them to join friendship groups where offending is normalised (Jo and Chesney-Lind, 1998;Sharpe, 2012) and to form 'relationships' with partners who exploit them (Cockbain and Brayley, 2012). Given the context of their lives and 'polyvictimization' (DeHart and Moran, 2015), young women's offending is increasingly depicted in the research literature as 'normal' or a display of agency (Sharpe, 2012;Henriksen and Miller, 2012;Batchelor, 2005), as are their 'difficult' attitudes (Alder, 2000;Sharpe, 2012).…”
Section: Introductionmentioning
confidence: 99%